Factors Affecting the Success Rate of Intrauterine Insemination in the Treatment of Subfertility Following Controlled Ovarian Hyperstimulation - Imran, Rabia; Baqai, Shehla; Siraj, Asifa; Khan, Sumaira; Urooj, Uzma; Zohra, Sadaf (Pakistan Armed Forces Medical Journal, 2023)
Objectives: To determine the success rate of Intrauterine Insemination following Controlled Ovarian Hyperstimulation inpatients with subfertility and to determine the frequency of prognostic factors affecting the success rate of this treatment modality. Study Design: Cross-sectional study. Place and Duration of Study: Department of Obstetrics & Gynecology, Pak-Emirates Military Hospital, Rawalpindi Pakistan, rom Feb to Aug 2019. Methodology: A total number of 135 sub-fertile patients, aged 18 to 40 years, with a duration of subfertility > 2 years, were included in the study. Couples with bilateral tubal blockade, smoking, combined male and female factor infertility and previous ovarian surgery were excluded. Controlled ovarian hyperstimulation was done with Clomiphene Citrate for five days, followed by ovulation triggered by recombinant human chorionic gonadotropin (HCG) and standard insemination with a prepared sample of the husband’s semen after 36 hours. Results: Success of the procedure was seen in 23(17.04%) patients, while the remaining 112(82.96%) were unsuccessful. The mean age was 29.20±4.90 years. Of 135 patients, 83(61.48%) had primary subfertility, and 52(38.52%) had secondary subfertility. The mean duration of subfertility was 5.60±3.35 years. The mean basal FSH was 5.76±2.54 IU/l. The mean number of IUI cycles was 1.39±0.49. Conclusion: This study concluded that the success rate of intrauterine insemination following controlled ovarian hyperstimulation in the treatment of subfertility was 17.04%, and the duration and type of subfertility, aetiology of subfertility, basal Follicle-stimulating hormone levels and the number of Intrauterine insemination cycles are the prognostic factors affecting the success of the procedure.